Welfare Effects of Income Taxation in a Model of Stochastic Growth - Christiane Clemens; Susanne Soretz (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 1997)
This paper analyzes growth and welfare effects of income taxation in a stochastic endogenous growth model with externalities in human-capital accumulation. The government participates in individual income risks by the collection of a flat-rate income tax that affects the mean and the variance of after-tax income. We examine the implications of a tax-transfer policy for the macroeconomic equilibrium of the economy. An increase in the tax rate on mean income has an unambiguously negative effect on the expected growth rate. Paradoxically, this may induce welfare gains. The opposite results can be derived for a rise in the tax rate on transitory income. These counter-intuitive results of the stochastic Arrow-Romer model can be ascribed to the specific int eraction of consumption and portfolio choice in the determination of growth and welfare.
Keywords: D8; D9; E6; G1; H2; O4; 330; endogenoues growth; taxation; uncertainty